2011
DOI: 10.1128/aac.00739-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Susceptibility of Bacterial Enteropathogens Isolated from International Travelers to Mexico, Guatemala, and India from 2006 to 2008

Abstract: The incidence rates of travelers' diarrhea (TD) have remained high for the last 50 years. More recently, there have been increasing recommendations for self-initiated therapy and use of prophylactic drugs for TD. We last examined the in vitro susceptibilities of commonly used antibiotics against TD pathogens in 1997. We now examine 456 enteropathogens isolated from adult travelers to Mexico, India, and Guatemala with diarrhea acquired between 2006 and 2008 to determine changes in susceptibility against 10 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…One study showed that azithromycin had high activity against TD pathogens but another suggested that concentrations needed to inhibit diarrheagenic E. coli have been increasing over the past decades. ( 26 ) In vitro studies showed increasing resistance among Campylobacter isolates in Nepal and Th ailand but clinical failures have not been reported ( 139 ).…”
Section: Th E Evidence Does Not Support Empiric Anti-microbial Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that azithromycin had high activity against TD pathogens but another suggested that concentrations needed to inhibit diarrheagenic E. coli have been increasing over the past decades. ( 26 ) In vitro studies showed increasing resistance among Campylobacter isolates in Nepal and Th ailand but clinical failures have not been reported ( 139 ).…”
Section: Th E Evidence Does Not Support Empiric Anti-microbial Therapymentioning
confidence: 99%
“…Th e emergence of fl uoroquinolone resistance to commonly encountered TD pathogens may be a factor today if these studies were replicated ( 139,247,248 ). Furthermore, relative to rifaximin, the safety profi le for fl oroquinolones is less favorable given the association with tendonopathies and the systemic broad-spectrum nature of this antibiotic with attendant pressures on systemic drug-resistant pathogens of importance ( 132 ).…”
Section: Prophylaxismentioning
confidence: 99%
“…(i) Treatment of traveler's diarrhea. Antibiotics are generally recommended for treatment of traveler's diarrhea, but because EAEC is increasingly resistant to various antibiotics, selection of the appropriate antibiotic should take into account the region of the world where the infection was acquired, as there are different antimicrobial susceptibility patterns for each geographical region (670)(671)(672). Like Shigella infections, EAEC infections are often successfully treated with ciprofloxacin and other fluoroquinolones, but there are multiple antibiotic-resistant strains (597,673).…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Travelers are advised to carry with them a fluoroquinolone antibiotic (ciprofloxacin) in case they develop severe diarrhea. Quinolones are contra-indicated in pregnancy, and quinolone-resistant campylobacter and other infections are prevalent in some countries especially in South Asia [47]. Azithromycin is recommended as an alternative antibiotic [48].…”
Section: Diarrheal Illness and Food And Water-borne Diseasesmentioning
confidence: 99%
“…In general, hot cooked food and sealed bottled liquids should be advised. Some of the most common bacterial pathogens associated with TD include campylobacter, salmonella, shigella and escherichia coli [46,47]. Travelers are advised to carry with them a fluoroquinolone antibiotic (ciprofloxacin) in case they develop severe diarrhea.…”
Section: Diarrheal Illness and Food And Water-borne Diseasesmentioning
confidence: 99%